Recent Progress in Autonomous Laboratories for Chemical Synthesis (Communications in Computational Chemistry, 2025)
The integration of artificial intelligence (AI) and robotics into chemical synthesis has given rise to autonomouslaboratories, transformative systems designed to overcome limitations in traditional experimental approaches. This reviewsynthesizes recent advancements in autonomous laboratory systems, highlighting their applications in chemical synthesis and theinnovations driving their evolution. Autonomous laboratories combine automated hardware, intelligent software, and adaptivesystems to optimize experimental workflows, reduce human intervention, and enhance efficiency in complex reactionenvironments. Key developments include AI-driven reaction pathway planning, closed-loop optimization frameworks, and roboticplatforms capable of executing multi-step synthesis with minimal expert oversight. Leading research groups have demonstratedsignificant progress, such as AI-guided discovery of functional materials, automated photocatalytic reaction optimization, andself-learning microfluidic systems. This review provides a comprehensive analysis of current achievements and remaining gaps,offering insights for researchers and policymakers in advancing this transformative technology.
Keywords: autonomous laboratory; chemical synthesis; artificial intelligence; machine learning